Measuring the through-plane and in-plane oxygen apparent diffusion coefficients in the gas diffusion layer - Yao, Keguang; Long, Tiehan; Wang, Yajun; Yuan, Xiao-Zi; Yao, Yao; Wang, Haijiang (Frontiers in Energy Research, 2023)
Oxygen diffusion coefficients in both in-plane and through-plane directions are significant to accurately predict the oxygen mass transport resistance in fuel cells, as well as the current distribution. However, so far, few methods have been established to measure the in-plane oxygen diffusion coefficient, even though it is an important parameter for the simulation of the oxygen flux distribution in gas diffusion layer (GDL). In this research, measurement methods and calculation of both in-plane and through-plane oxygen diffusion coefficients are established. Using the in-house designed cells, both the in-plane and through-plane oxygen apparent diffusion coefficients of a commercial carbon paper (AvCarb EP40) at various torques and gas flow rates are measured, and the oxygen flux distributions in GDL under each torques and gas flow rates are simulated. The results indicate that the channel part is the major contribution to the total oxygen flux at high torques condition, and the increase in the torques would lead to a decrease of the contribution from the landing part to the total oxygen flux. The simulation results also suggest that a higher gas flow rate and a lower torque would contribute to a more uniform distribution of the oxygen flux in the GDL.